Direct synthesis of graphene from adsorbed organic solvent molecules over copper1. Issue 75 (19th August 2015) - Pang, Jinbo; Bachmatiuk, Alicja; Fu, Lei; Mendes, Rafael G.; Libera, Marcin; Placha, Daniela; Martynková, Grazyna Simha; Trzebicka, Barbara; Gemming, Thomas; Eckert, Juergen; Rümmeli, Mark H.
<x xml:space="preserve">Abstract</x> We show the direct synthesis of graphene from adsorbed organic solvent molecules over copper by annealing in hydrogen.